HUBUNGAN PERAN ORANG TUA TERHADAP PERKEMBANGAN MENTAL-EMOSIONAL - Aditya, Ahmad Nuzul; Indriati, Ganis; Fitri, Aminatul (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
Background: Mental-emotional development of preschool influenced by various factors, one is role of parents. This study aims to determine the relationship between role of parents and mental-emotional development. Methods: this study uses correlative descriptive design with cross sectional approach. The research sample was 97 respondents taken by purposive sampling technique. This study uses a questionnaire Questionnaire Mental Emotional Problems and Role of Parents which has been tested for validity and reliability. The analysis used is chi-square. Results: The study showed that majority of parents were aged 26-35 years (68.0%), their parents had high school education level (64.9%), and the majority of their parents were housewives (62.9%), the majority of children aged 4 years (41.2%), more than half of the sex of boys (62.9%), the role of parents is low (54.6%), and the possibility of children experiencing mental-emotional problems (58.8% ). The results of the chi-square showed that there was a relationship between the role of parents and the mental-emotional development of preschoolers (p value 0.000: alpha 0.05). Conclusion: Role of parents affects the mental-emotional development of the child's development to be optimal. Researchers recommend parents to seek more knowledge about children's mental-emotional development, so that children's development will be optimal.